Vpliv emulzije PVA na izpiranje bora in bakra iz lesa ter na učinkovitost delovanja proti glivam razkrojevalkam lesa - Lesar, Boštjan (Zbornik gozdarstva in lesarstva, 2007)
Boron compounds are very effective fungicides, but they leach from wood in wet environments, unfortunately. In order to improve boron fixation, boric acid, borax and copper(II) sulphate were combined with polyvinyl acetate emulsion (PVA). Selected preservative solutions were chosen for impregnation of Norway spruce wood specimens (Picea abies). Wood blocks were exposed to three wood decay fungi Antrodia vaillantii, Gloeophyllum trabeum and Trametes versicolor according to the mini block procedure. Part of impregnated specimens was leached according to the EN 1250-2 procedure. The results showed that addition of PVA emulsion slightly improves copper and boron fixation. Spruce wood impregnated with the lowest concentration of boron based solutions (cB = 0.1%) was found resistant against tested fungi. In contrast, wood blocks impregnated with copper were sufficiently protected against G. trabeum and T. versicolor but not against A. vaillantii. Furthermore, PVA itself has a negative impact on fungal growth, and it improves performance of boron and copper based aqueous solutions.
Keywords: baker; bor; emulzije; impregnacija; lastnosti; zaščita lesa